2020
DOI: 10.3389/fvets.2020.580356
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Assessment of Individual Paranasal Sinus Compartment and Nasal Conchal Bulla Involvement in 300 Cases of Equine Sinonasal Disease

Abstract: Background: Computed tomographic (CT) imaging has allowed new anatomical studies and detailed clinical imaging of the complex, overlapping equine sinonasal structures. Despite the widespread use of CT, no study has specifically identified which compartments are most commonly affected with sinus disorders. CT has also shown the presence of intercurrent, ipsilateral nasal disorders, especially infection of the nasal conchal bullae (NCB) in many cases of sinus disease, but the frequency of intercurrent NCB infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…This is likely due to increasing awareness of these middle meatus lesions, the use of CT 13 and more careful endoscopic examination of this area. A recent multicentre CT study of 300 horses found an overall prevalence of NCB lesions (infection or loss) in 56% of horses with sinus disease 5 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is likely due to increasing awareness of these middle meatus lesions, the use of CT 13 and more careful endoscopic examination of this area. A recent multicentre CT study of 300 horses found an overall prevalence of NCB lesions (infection or loss) in 56% of horses with sinus disease 5 …”
Section: Discussionmentioning
confidence: 99%
“…However, those treatments usually involved sinusotomy and nasal fistulation, that along with prolonged sinus lavage, likely dislodged inspissated exudate and sequestrae from the middle meatus or NCB, as well as from the sinuses, thus resolving any concurrent nasal problem. The presence of complete loss of NCB with distortion and adjacent nasal conchal changes in some horses with sinusitis 5 indicates that some infected NCBs are fully lost, thus allowing resolution of the nasal middle meatus inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging of the equine head with MDCT has been well described 7,16–25 and comparisons between MDCT and CBCT have been reported in the human literature 11,14,15,26 . Sparse information is available on their comparison in small animal imaging 12,27,28 and no studies have compared CBCT and MDCT for equine head imaging.…”
Section: Introductionmentioning
confidence: 99%